Surgical Outcome of Anterior Cervical Disectomy and Fusion Using Peek Cage for Cervical Disc Herniation in Terms of Pain Relief (Medical Forum Monthly, 2021)
Objective: The purpose of this study was to evaluate the outcome of anterior cervical discectomy and fusion (ACDF) using a PEEK cage.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the Neurosurgery Department, Bacha Khan Medical College, Mardan Medical Complex, Peshawar from December 2017 until December 2020.Materials and Methods: The study excluded patients who required multiple level ACDF or corpectomy with plating and redo instances. A proforma was completed that covered the patient's age, gender, address, level of prolapsed disc, signs and symptoms, pain score, and MRI findings. All patients were evaluated on the day of discharge and during a one-month follow-up visit. SPSS version 22 was used to analyze the data.Results: A total of 53 patients were included, including 62.26% males and 37.73% females. Patients ranged in age from 27 to 64 years, with a mean of 50.4 years. (61%) patients had radicular pain on the right side. Radiculomyelopathy was present in patients with 5.26 percent. C5–C6 was the most often operated level (35 patients). Using Odom's criteria, excellent results were obtained in 81 percent individuals and adequate results in the remaining patients. At six months, 92 percent of patients had a fusion of the bones.Conclusion: ACDF with PEEK cage fixation is a safe and beneficial treatment for cervical prolapse disc disease at one level.